FcɛR1α gene polymorphism shows association with high IgE and anti‐FcɛR1α in Chronic Rhinosinusitis with Nasal Polyposis. Issue 5 (22nd January 2018) - Dar, Sajad A.; Rai, Gargi; Ansari, Mohammad A.; Akhter, Naseem; Gupta, Neelima; Sharma, Sonal; Haque, Shafiul; Ramachandran, Vishnampettai G.; Wahid, Mohd; Rudramurthy, Shivprakash M.; Chakrabarti, Arunaloke; Das, Shukla
Abstract: Despite large number of investigations, the etiology of chronic rhinosinusitis (CRS) remains unclear. Several factors are likely involved in its onset. The genetic susceptibility of IgE‐responsiveness likely caused by polymorphism(s) in high affinity receptor for IgE (FcɛR1α) gene can help in understanding the pathophysiology of CRS with nasal polyposis (CRSwNP). A population‐based case‐control association analysis was conducted to assess the risk of CRSwNP conferred by single nucleotide polymorphisms (SNPs) in FcɛR1α gene in a North Indian cohort. Two promoter and three exonic regions of FcɛR1α gene were amplified and sequenced to investigate five SNPs: rs2427827, rs2251746, rs2298804, rs2298805, and rs2269718. BLAST analysis and subsequent multiple alignments, with known sequences available in the NCBI database, were performed. Total serum IgE and FcɛR1α antibody levels were estimated. Patient IgE level of 461.22 ± 436.43 in comparison to 83.62 ± 58.043 IU/mL in controls ( P < 0.0001), and FcɛR1α antibody level of 292.38 ± 115.27 in comparison to 160.56 ± 105.9 in controls ( P < 0.0001), depicts their highly significant associations with CRSwNP disease. However, no SNP showed evidence of association with CRSwNP; although relatively higher Odds ratios were observed with rs2427827, rs2251746, and rs2298804. Patient stratification revealed a significant association ( P < 0.05) of rs2427827 SNP with high IgE level CRSwNP patients. Nonetheless, we found no SNP associated with low serum IgE level patients. SNP (rs2427827) in the FcɛR1α gene region and high IgE levels may confer susceptibility to CRSwNP in north Indian population. However, further studies including larger sample size, gene‐gene, and gene‐environment interactions are required for its elucidation. Abstract : The genetic susceptibility of IgE‐responsiveness likely caused by polymorphism(s) in FcɛR1α gene can help in understanding the pathophysiology of CRSwNP. We conducted a population‐based case‐control association analysis to assess the risk of CRSwNP conferred by SNPs (rs2427827, rs2251746, rs2298804, rs2298805, and rs2269718) in FcɛR1α gene in a north Indian cohort. Patient stratification revealed a significant association ( P < 0.05) of rs2427827 SNP with high IgE level in CRSwNP patients which may confer susceptibility to CRSwNP in the studied population.